Representasi Kritik Sosial dalam Film Lafran dan Implikasinya terhadap Pembelajaran Bahasa Indonesia di SMA - Naqiyah, Nuril Kamilatin; Quthny, Abu Yazid Adnan; Hikam, Ahmad Ilzamul (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2025)
The film Lafran presents the intellectual and social journey of a figure who has critical thinking about the social political condition of Indonesia. In this study, a Marxist perspective is used to analyze the social criticsm that appears in the film’s narrative, including how class inequality, economic exploitation, political system, education, and social system, as well the dynamics of intellectual struggle are represented. This film not only depicts the struggle of individuals in facing an oppressive system, but also shows how social structures shape critical awarenes in society. In addition to being a social reflection, the film Lafran Pane has relevance to learning Indonesian, especially thinking skills towards texts and discourse. Learning indonesiann does not only focus on linguistic the social, cultural, and ideological contexts contained in various types of texts. By sudents can develop critical awareness in understanding the structure and meaning of language, as well as recognizing how a cultural work can represent social and political realities. The study aims to connect Marxist social criticsm in film with appoarch to learning indonesiian, so that it can provide insight into how visual media such as film can be used as an educational tool in improving students understanding of social and language dynamics.